Pharmacological Basis of the Clinical Efficacy of Varenicline Used to Facilitate Smoking Cessation - S. R. Gilyarevskiy (Столичная издательская компания, 2019)
Modern problems caused by the high prevalence of smoking, as well as pharmacological approaches that facilitate quitting smoking are discussed in the review. Data on the mechanisms of formation of nicotine addiction, which determine the choice of drug interventions aimed at increasing the probability of quitting smoking are presented. The pharmacological characteristics of the most commonly used drugs used to facilitate smoking cessation are given. Special attention is paid to data on the mechanisms of action of varenicline and evidence of its clinical efficacy and safety, including in patients with concomitant cardiovascular diseases, as well as in patients with a history of acute coronary syndrome. Evidence on the effectiveness of the combined use of varenicline and nicotine replacement therapy are presented.